Strengthening capacity on Orange-fleshed Sweetpotato through training of trainers efforts in West Africa - International Potato Center (2017)
Under the “Jumpstarting Orange-fleshed Sweetpotato (OFSP) in West Africa through Diversified Markets” project, we used a training of trainers (ToT) approach to build capacity along value chains in Ghana, Nigeria, and Burkina Faso. Diverse training efforts ensured success of the project, and established a base for going to scale in each country.